The longitudinal effects of the built environment on transportation and recreational walking, and differences by age and sex: systematic review protocol - Tharindu Niwarthana Bandara; Carl Higgs; Belen Zapata-Diomedi; Lucy Gunn; Gavin Turrell; Alysha De Livera (BMC, 2023)
Abstract Background In high-income countries, the prevalence of physical inactivity and non-communicable diseases is high, and it is now well-established that insufficient physical activity is a risk factor for non-communicable diseases. Walking for recreation and transportation are effective means of improving population levels of physical activity. Research finds that the built environment (BE) can encourage or discourage walking behaviour, and this association varies for different age groups and sexes. This systematic review aims to synthesise longitudinal evidence to better understand how the BE affects recreational and transportation walking for different age groups (above 64 years and 18-64 years) and sexes in high-income countries. Method We will use Scopus, PubMed, SPORTDiscus with Full Text (EBSCO), Business Source Complete (EBSCO), Art and Architecture Archive (Proquest), Avery Index to Architectural Periodicals (ProQuest), and Art, Design & Architecture Collection (ProQuest) databases to search for relevant studies. Reviewers will screen the search results according to pre-specified eligibility criteria for study inclusion in the review. Required data for the synthesis will be extracted from the included studies to answer the research questions. Further, the methodological quality of the studies included in this systematic review will be evaluated using an established instrument, and the resulting quality scores will be utilized in sensitivity analysis. The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) checklist will be followed when reporting the findings. Discussion This review will identify BE attributes that are likely to influence transportation and recreational walking for younger and older adults and different sexes in high-income countries. The findings will help policymakers with making decisions around walkable built environments for older and younger adults and different sexes to keep them healthy. Trial registration This protocol of the prospective systematic review is developed following PRISMA-P guidelines and is registered on the Prospective Register of Systematic Reviews (PROSPERO) (registration ID CRD42022351919).